Metal complex hydroxide powder, production method of positive-electrode active material for lithium secondary battery, and production method of metal complex hydroxide powder
By controlling carbon content and surface area through a specific production process, the method enhances the initial efficiency and stability of lithium secondary batteries by reducing lithium carbonate residuals in the positive active material.
Patent Information
- Application Number
- JP2023113643
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for manufacturing positive active materials for lithium secondary batteries do not effectively reduce the content of lithium carbonate and improve the initial efficiency of the batteries.
The method involves producing metal composite hydroxide powder with controlled carbon content and surface area, using a specific production process that includes heating a wet cake containing metal composite hydroxide to reduce carbon content and enhance surface smoothness, resulting in a powder with low carbon impurities and improved reactivity.
This approach reduces the amount of lithium carbonate residual in the positive active material, leading to higher initial efficiency and stability of lithium secondary batteries.
Smart Images

Figure 2025011494000002 
Figure 2025011494000003 
Figure 2025011494000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal composite hydroxide powder, a method for producing a positive electrode active material for a lithium secondary battery, and a method for producing a metal composite hydroxide powder. [Background technology]
[0002] For the purpose of improving the performance of positive electrode active materials for lithium secondary batteries, attempts have been made to control various aspects of the manufacturing process for positive electrode active materials for lithium secondary batteries.
[0003] For example, Patent Document 1 describes a method for producing a positive electrode active material for a lithium secondary battery, which includes a step of adjusting the particle size distribution of a metal composite hydroxide by pulverizing a hydroxide raw material powder corresponding to the metal composite hydroxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2014 / 061580A1 Summary of the Invention [Problem to be solved by the invention]
[0005] From the viewpoint of improving the initial efficiency of lithium secondary batteries, there is room for further improvement in the physical properties of metal composite hydroxides, which are raw materials for positive electrode active materials for lithium secondary batteries.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a metal composite hydroxide powder that can reduce the amount of lithium carbonate remaining in a positive electrode active material and can provide a lithium secondary battery with high initial efficiency, a method for producing a positive electrode active material for a lithium secondary battery, and a method for producing a metal composite hydroxide powder. [Means for solving the problem]
[0007] The present inventors have noticed that the content of carbon element (C) in the metal composite hydroxide powder is affected by the surface state of the metal composite hydroxide. The present invention has the following aspects. [1] A metal composite hydroxide powder containing at least Ni, the metal composite hydroxide powder having a BET specific surface area of 10 m 2 / g, the content of carbon atoms (C) contained in the metal composite hydroxide powder is 0.1 mass% or less with respect to the total mass of the metal composite hydroxide powder, and when the metal composite hydroxide powder is exposed to the atmosphere for 2 hours, the rate of increase in the C content is less than 0.05 mass% / h. [2] The metal composite hydroxide powder according to [1], wherein the average secondary particle size of the metal composite hydroxide powder is 5 μm or more and 20 μm or less. [3] The metal composite hydroxide powder according to [1] or [2], further containing an element M, wherein the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P. [4] A method for producing a positive electrode active material for a lithium secondary battery, comprising calcining a mixture of the metal composite hydroxide powder according to any one of [1] to [3] and a lithium compound. [5] A method for producing a metal composite hydroxide powder, comprising a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni, 2 / g, a content of carbon atoms (C) contained in the metal composite hydroxide powder is 0.1 mass% or less with respect to a total mass of the metal composite hydroxide, and when the metal composite hydroxide powder obtained in the step X is exposed to the atmosphere for 2 hours, a rate of increase in the C content is less than 0.05 mass% / h. [6] The method for producing a metal composite hydroxide powder according to [5], wherein the average secondary particle size of the metal composite hydroxide powder is 5 μm or more and 20 μm or less. [7] The method for producing a metal composite hydroxide powder according to [5] or [6], wherein the metal composite hydroxide powder further contains an element M, and the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P. Effect of the Invention
[0008] Effects of the Invention According to the present invention, it is possible to provide a metal composite hydroxide powder that can reduce the amount of lithium carbonate remaining in a positive electrode active material and can provide a lithium secondary battery with high initial efficiency, a method for producing a positive electrode active material for a lithium secondary battery, and a method for producing a metal composite hydroxide powder. [Brief description of the drawings]
[0009] [Figure 1] 1 is a scanning electron microscope image of a metal composite hydroxide powder according to one aspect of this embodiment. [Diagram 2] 1 is a scanning electron microscope image of a metal composite hydroxide powder in which the rate of increase in the C content is 0.05 mass % / h or more. [Diagram 3] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Figure 4] FIG. 1 is a schematic diagram illustrating an example of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the metal composite hydroxide powder according to one aspect of the present invention will be described. In the following embodiments, preferred examples and conditions may be shared. In addition, in this specification, each term is defined as follows.
[0011] In this specification, the metal composite hydroxide powder is hereinafter referred to as "Powder Y", and the cathode active material for lithium secondary batteries is hereinafter referred to as "CAM".
[0012] "Ni" refers to nickel atoms, not nickel metal. Similarly, "Co" and "Al" refer to cobalt atoms and aluminum atoms, etc., respectively. "C" refers to carbon atoms.
[0013] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.
[0014] The "cumulative volumetric particle size" is a value measured by a laser diffraction scattering method. Specifically, 0.1 g of powder Y is added to 50 ml of a 0.2 mass % aqueous solution of sodium hexametaphosphate to obtain a dispersion in which the powder Y is dispersed. Next, the particle size distribution of the obtained dispersion is measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments) to obtain a volume-based cumulative particle size distribution curve. In the obtained cumulative particle size distribution curve, the particle diameter value at 50% accumulation from the fine particle side is called the 50% cumulative volumetric particle size (hereinafter, D 50 and is the average secondary particle size (μm) of powder Y in this specification.
[0015] "BET specific surface area" is a value measured by the BET (Brunauer, Emmett, Teller) method. In measuring the BET specific surface area, nitrogen gas is used as the adsorption gas. For example, 1 g of powder Y is dried in a nitrogen atmosphere at 105°C for 30 minutes, and then the BET specific surface area can be measured using a BET specific surface area meter (for example, Macsorb (registered trademark) manufactured by Mountec Co., Ltd.) (unit: m 2 / g).
[0016] The "composition analysis of powder Y" is performed by the following method. For example, powder Y is dissolved in hydrochloric acid, and then the composition is measured using an ICP emission spectrometer. As the ICP emission spectrometer, for example, Optima 7300 manufactured by PerkinElmer Co., Ltd. can be used.
[0017] The amount of lithium carbonate remaining in CAM is sometimes called the "amount of residual lithium carbonate." The "amount of residual lithium carbonate" is measured by neutralization titration. Specifically, 20 g of CAM and 100 g of ion-exchanged water are placed in a 100 ml beaker and stirred for 5 minutes. After stirring, the CAM is filtered, 0.1 mol / L hydrochloric acid is dropped into 60 g of the remaining filtrate, and the pH of the filtrate is measured with a pH meter. The titration amount of hydrochloric acid from the start of the titration to the first end point (pH = 8.30) is A ml, and the titration amount of hydrochloric acid from the first end point (pH = 8.30) to the second end point (pH = 4.50) is B ml. The concentrations of lithium carbonate and lithium hydroxide remaining in CAM are calculated using the following formula. In the following formula, the molecular weights of lithium carbonate and lithium hydroxide are calculated using the atomic weights of H; 1.000, Li; 6.941, C; 12, and O; 16. The sum of the lithium carbonate concentration and the lithium hydroxide concentration obtained by the following calculation formula is defined as the amount of residual lithium carbonate (mass%). Lithium carbonate concentration (mass%) = {0.1×(BA) / 1000}×{73.882 / (20×60 / 100)×100} Lithium hydroxide concentration (mass%) = {0.1×(2A-B) / 1000}×{23.941 / (20×60 / 100)×100}
[0018] The "initial efficiency" refers to a value measured by charging and discharging a lithium secondary battery under the following conditions.
[0019] (Charge / discharge test) Test temperature: 25℃ Maximum charging voltage 4.3V, charging current 0.2CA, constant current constant voltage charging Minimum discharge voltage 2.5V, discharge current 0.2CA, constant current discharge (First-stage efficiency) Initial efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g) x 100
[0020] In measuring the initial efficiency, a lithium secondary battery prepared by the following method is used. (Preparation of positive electrodes for lithium secondary batteries) A paste-like positive electrode mixture is prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) so that the composition is CAM:conductive material:binder = 92:5:3 (mass ratio). When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.
[0021] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.
[0022] (Production of lithium secondary batteries) The following operations are carried out in a glove box under an argon atmosphere. The positive electrode for lithium secondary batteries prepared in (Preparation of positive electrode for lithium secondary batteries) is placed with the aluminum foil side facing down on the bottom cover of a part for coin-type battery R2032 (manufactured by Hosen Co., Ltd.), and a laminated film separator (a 16μm-thick laminate of a heat-resistant porous layer laminated on a polyethylene porous film) is placed on top of it. 300μl of electrolyte is poured here. The electrolyte used is a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a 30:35:35 (volume ratio) mixture in which LiPF6 is dissolved to make 1mol / l. Next, metallic lithium is used as the negative electrode, and the negative electrode is placed on the upper side of a laminated film separator, and a top lid is placed on the negative electrode via a gasket, and the battery is crimped with a crimping machine to prepare a lithium secondary battery (coin-type half cell R2032).
[0023] <Metal composite hydroxide powder> In one embodiment of the present invention, the powder Y contains at least Ni, and the BET specific surface area of the powder Y is 10 m 2 / g, the content of C contained in the powder Y is 0.1 mass% or less with respect to the total mass of the powder Y, and the rate of increase of the content of C when the powder Y is exposed to the atmosphere for 2 hours is less than 0.05 mass% / h.
[0024] The powder Y is composed of a plurality of particles. The powder Y may contain only secondary particles, or may be a mixture of primary particles and secondary particles.
[0025] Here, the term "primary particle" refers to a particle that does not have grain boundaries in appearance and that constitutes a secondary particle. More specifically, the term "primary particle" refers to a particle that does not have clear grain boundaries on the particle surface when observed at a magnification of 5000 to 20000 times using a scanning electron microscope or the like. The term "secondary particle" refers to a particle formed by agglomeration of the primary particles. In other words, the secondary particle is an agglomeration of the primary particles.
[0026] The content of C contained in the powder Y is preferably 0.09% by mass or less with respect to the total mass of the powder Y. The lower limit of the content of C is, for example, 0.005% by mass. When the content of C is within the above range, it can be said that the impurities contained in the powder Y are small. Examples of the impurities include carbon dioxide, nickel carbonate, and sodium carbonate. The amount of residual lithium carbonate contained in the CAM produced using this powder Y as a raw material can be reduced. Specifically, the amount of residual lithium carbonate contained in the powder Y can be made less than 0.8% by mass with respect to the total mass of the CAM. A lithium secondary battery using such a CAM has a small amount of gas generation and a high cycle retention rate. In addition, when the powder Y having a content of C within the above range is used, the initial efficiency of the lithium secondary battery can be improved. The C content is preferably 0.005-0.1 mass %, more preferably 0.005-0.09 mass %.
[0027] The C content in Powder Y is the amount measured after leaving Powder Y obtained by the manufacturing method described below in the air for 24 hours or more.
[0028] The rate of increase in the C content is small, less than 0.05 mass% / h. Here, the rate of increase in the C content refers to the rate of increase in C from the time immediately after the step X described below, or from the time when the powder Y stored in a container or the like without exposure to the air immediately after the step X is exposed to the air until 2 hours have elapsed. A specific method for measuring the rate of increase in the C content will be described below.
[0029] (Increase in C content) Two samples of powder Y stored in a container or the like without exposure to air immediately after the step X described below or immediately after the step X are sampled, and the C content of one of the powders Y is immediately measured. The time when the C content of one of the powders Y is measured is set to 0 hours. The other powder Y is exposed to the air, and the C content after 2 hours is measured. The increase rate of the C content is calculated by dividing the difference between the C content of powder Y after 2 hours and the C content of the one of the powders Y by 2. In this specification, "immediately after the step X" means within 30 minutes from immediately after the powder is discharged from the outlet of the device performing the step X, for example, a fluidized drying device.
[0030] (Measurement of C content) The C content in the powder Y is measured by an infrared combustion method. Specifically, it is measured using a carbon / sulfur analyzer (for example, product name: EMIA-320V2, manufactured by HORIBA).
[0031] The rate of increase in the C content is more preferably 0.04 mass% / h or less. The lower limit of the rate of increase in the C content is, for example, 0.002 mass% / h. When the rate of increase in the C content is within the above range, it can be said that the powder Y has high stability until it is used for the production of CAM. The CAM obtained by using such powder Y can reduce the amount of residual lithium carbonate and can improve the initial efficiency of the lithium secondary battery. The rate of increase in the C content is preferably 0.002 mass% / h or more and less than 0.05 mass% / h, and more preferably 0.002 to 0.04 mass% / h.
[0032] One of the reasons why the rate of increase in the C content is less than 0.05 mass% / h is the smooth surface of Powder Y. This makes it difficult for carbon dioxide in the air to be adsorbed onto the surface of Powder Y, and metal carbonates produced by the reaction between metal elements contained in Powder Y and carbon dioxide are less likely to be produced, which is thought to make it difficult for the C content in Powder Y to increase.
[0033] Figure 1 is a scanning electron microscope (SEM) image of Powder Y in which the rate of increase in the C content is less than 0.05 mass% / h. Figure 2 is a SEM image of Powder Y in which the rate of increase in the C content is 0.05 mass% / h or more. Powder Y in Figure 1 has a smoother surface than Powder Y in Figure 2.
[0034] The BET specific surface area of powder Y is 12m 2 / g or more, and 15m 2 / g or more is more preferable, and 17m 2 When the BET specific surface area of the powder Y is equal to or greater than the lower limit, the reactivity with the lithium compound is improved, the amount of residual lithium carbonate in the obtained CAM can be reduced, and the initial efficiency of the lithium secondary battery tends to be high. 2 / g or less, and 2 / g or less is more preferable, 2 The upper and lower limits of the BET specific surface area of the powder Y can be arbitrarily combined, and the upper and lower limits are preferably within 10 m 2 / g greater than 50m 2 / g or less, and 12-49m 2 / g is more preferable, 15-48m 2 / g is more preferable, and 17-48m 2 / g is even more preferred.
[0035] D is the average secondary particle diameter of powder Y 50 is preferably 5 μm or more, more preferably 9 μm or more, and even more preferably 9.5 μm or more. 50 is preferably 20 μm or less, and more preferably 18 μm or less. 50 is preferably 5-20 μm, more preferably 9-20 μm, and even more preferably 9.5-18 μm. 50 When the content of the CAM is within the above range, an increase in the resistance of the resulting CAM is suppressed, which contributes to an improvement in the initial efficiency of the lithium secondary battery.
[0036] Powder Y contains at least Ni, and preferably contains Ni and element M. Element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S, and P. From the perspective of obtaining a lithium secondary battery with high cycle retention and initial efficiency, element M is preferably one or more elements selected from the group consisting of Mn, Co, Al, Ti, Mg, W, B, Nb, and Zr. Powder Y may contain two or more kinds of element M. Powder Y substantially does not contain Li.
[0037] The metal composite hydroxide contained in powder Y preferably contains Ni and the element M in the molar ratio represented by the following formula (A), and is preferably represented by the following formula (A’). Ni:M = (1 - x):x (A) Ni (1-x) M x (OH)2 (A’) (In formula (A) and formula (A’), M is the element M, and formula (A) and formula (A’) satisfy 0 < x ≤ 0.5.)
[0038] From the perspective of obtaining a lithium secondary battery with a large battery capacity, x in the above formula (A) and formula (A’) is preferably more than 0 and 0.50 or less, more preferably more than 0 and 0.40 or less, still more preferably more than 0 and 0.30 or less, and particularly preferably more than 0 and 0.25 or less.
[0039] The metal composite hydroxide more preferably contains Ni and element M1 in the molar ratio represented by the following formula (B), and is more preferably represented by the following formula (B’). Ni:M1:M2 = (1 - y - z):y:z (B) Ni (1-y-z) M1 y M2 z (OH)2 (B’) (In Formulas (B) and (B’), M1 is one or more elements selected from the group consisting of Co, Mn, and Al; M2 is one or more elements selected from the group consisting of Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S, and P; and Formulas (B) and (B’) satisfy 0 < y ≦ 0.5, 0 ≦ z ≦ 0.1, and 0 < y + z ≦ 0.5.)
[0040] From the viewpoint of obtaining a lithium secondary battery with a large battery capacity, the lower limit value of y is preferably 0.01. The upper limit value of y is preferably 0.30 or less, more preferably 0.20 or less, and even more preferably 0.15 or less. The upper and lower limit values of y can be arbitrarily combined. y is preferably more than 0 and not more than -0.30, more preferably 0.01 - 0.20, and even more preferably 0.01 - 0.15.
[0041] When the metal composite hydroxide contains the above M2, from the viewpoint of obtaining a lithium secondary battery with good cycle characteristics, the lower limit value of z is preferably more than 0 and 0.01. From the viewpoint of obtaining a lithium secondary battery with a large battery capacity, the upper limit value of z is preferably 0.10, more preferably 0.08. The upper and lower limit values of z can be arbitrarily combined. z is preferably 0 - 0.10, more preferably more than 0 and not more than 0.10, and even more preferably 0.01 - 0.08.
[0042] <Production of Powder Y> The method for producing powder Y in one embodiment of the present invention includes a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni, the BET specific surface area of powder Y is larger than 10 m 2 / g, the content of C contained in powder Y is 0.1 mass% or less based on the total mass of powder Y, and when the powder Y obtained in the step X is exposed to the atmosphere for 2 hours, the acceleration rate of the content of C is less than 0.05 mass% / h. In the method for producing powder Y, the preferable ranges of the BET specific surface area, the content of C, and the acceleration rate of the content of C of powder Y are the same as the above ranges, respectively. The step X is preferably a step of heating the wet cake while fluidizing it, and scraping the surface of the metal composite hydroxide contained in the wet cake. At this time, the ratio of the moisture contained in the wet cake immediately before the step X is preferably 5-25% by mass with respect to the total mass of the wet cake, and the ratio of the moisture contained in the wet cake immediately before the step X to the residence time of the wet cake in the heating device is preferably 11% by mass / hour or less. "Immediately before the step X" means within 30 minutes before carrying out the step X, and "immediately after the step X" means within 30 minutes from immediately after the wet cake is discharged from the outlet of a device for carrying out the step X, such as a fluidized drying device.
[0043] Here, the "moisture content of the wet cake and powder Y" can be calculated from the weight loss measured by a heat drying method using an infrared moisture meter, using the following formula (3). Note that the amount of the sample to be measured in the following formula (3) is the amount of the wet cake or powder Y. Moisture content (mass%) = weight loss (g) / measured sample weight (g) × 100 … (3)
[0044] Hereinafter, a method for producing the powder Y containing Ni and the element M will be described as an example.
[0045] First, prepare a metal composite hydroxide containing Ni and the element M. The metal composite hydroxide can be produced by a batch co-precipitation method or a continuous co-precipitation method.
[0046] Specifically, a nickel salt solution, a metal salt solution of element M, and a complexing agent are reacted by the continuous coprecipitation method described in JP-A-2002-201028 to produce powder Y containing the metal composite hydroxide represented by the formula (A'). For example, a nickel salt solution, a cobalt salt solution, an aluminum salt solution, and a complexing agent are reacted to produce Ni (1-x) Al a Co b A powder containing a metal composite hydroxide represented by (OH)2 (a+b=x) is produced.
[0047] The nickel salt that is the solute of the nickel salt solution is not particularly limited, but for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0048] As the aluminum salt which is the solute of the aluminum salt solution, for example, at least one of aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum acetate can be used.
[0049] As the cobalt salt which is the solute of the cobalt salt solution, for example, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate can be used.
[0050] The metal salt solutions are used in a ratio corresponding to the composition ratio of the above formula (A). That is, the amount of each metal salt solution is specified so that the molar ratio of Ni and element M in the mixed solution containing the above metal salts corresponds to (1-x):x. Water is used as the solvent.
[0051] The complexing agent is capable of forming a complex with nickel ions and ions of element M (e.g., aluminum ions and cobalt ions) in an aqueous solution, and examples thereof include ammonium ion donors (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracil diacetic acid, and glycine.
[0052] A complexing agent may or may not be used. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution containing the nickel salt solution, the metal salt solution of element M, and the complexing agent is, for example, a molar ratio of the complexing agent to the total number of moles of the metal salts (nickel salt, metal salt of element M) that is greater than 0 and less than or equal to 2.0.
[0053] In the coprecipitation method, in order to adjust the pH value of the mixture containing the nickel salt solution, the metal salt solution of element M, and the complexing agent, an alkali metal hydroxide is added to the mixture before the pH of the mixture becomes neutral from alkaline. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0054] In this specification, the pH value is defined as the value measured when the temperature of the mixed liquid is 40° C. If the temperature of the mixed liquid sampled from the reaction tank is not 40° C., the mixed liquid is heated or cooled to 40° C. before measuring the pH.
[0055] When the nickel salt solution, the metal salt solution of element M, and a complexing agent are continuously supplied to the reaction vessel, a metal composite hydroxide represented by formula (A') is produced.
[0056] During the reaction, the temperature of the mixture in the reaction vessel is controlled within the range of preferably 20-80°C, more preferably 30-70°C.
[0057] During the reaction, the pH value of the mixture in the reaction tank is set within the range of preferably 9 to 13, more preferably 10 to 12.5, and even more preferably 10 to 12, and the pH is controlled within ±0.5.
[0058] The reaction vessel used in the continuous coprecipitation method may be an overflow type reaction vessel for separating the reaction precipitate formed.
[0059] When a metal composite hydroxide is produced by a batch coprecipitation method, examples of the reaction tank include a reaction tank that is not equipped with an overflow pipe, and an apparatus that has a mechanism for concentrating the overflowed reaction precipitate in a concentration tank connected to an overflow pipe and circulating it back to the reaction tank.
[0060] Various gases may be supplied into the reaction vessel, for example, inert gases such as nitrogen, argon or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof.
[0061] By appropriately controlling the concentration of the metal salt supplied to the reaction tank, the temperature of the reaction tank, the pH of the mixed liquid in the reaction tank, etc., the D 50 can be controlled.
[0062] After the above reaction, the neutralized reaction precipitate is washed. The reaction precipitate is preferably washed with water or an alkaline washing solution. As the alkaline washing solution, an aqueous sodium hydroxide solution is preferable. Also, washing may be performed using a washing solution containing elemental sulfur. As an example of a washing solution containing elemental sulfur, an aqueous solution of potassium or sodium sulfate can be given. As a result, a wet cake containing a metal composite hydroxide is obtained.
[0063] After producing the wet cake, it is preferable to remove moisture from the wet cake before the step X so that the ratio of moisture contained in the wet cake is 5-25% by mass relative to the total mass of the wet cake. Examples of a method for removing moisture include centrifugation and suction filtration. The ratio of moisture contained in the wet cake immediately before the step X is preferably 5-23% by mass, more preferably 5-21% by mass relative to the total mass of the wet cake. If the ratio of moisture contained in the wet cake is 5% by mass or more relative to the total mass of the wet cake, the wet cake will be in a moderately moist state in the next step X, and the wet cake will flow, so that the surface of the metal composite hydroxide is easily scraped. If the ratio of moisture contained in the wet cake is 25% by mass or less relative to the total mass of the wet cake, the surface of the metal composite hydroxide is easily scraped in the step X, and moisture can be sufficiently removed. As a result, it is possible to produce powder Y in which the content of C and the rate of increase in the content of C are in the above-mentioned ranges. In addition, the amount of residual lithium carbonate in the CAM using powder Y can be reduced, and the initial efficiency of the lithium secondary battery can be improved.
[0064] In step X, the wet cake is heated while being fluidized, and the surface of the metal composite hydroxide is scraped. By heating, the moisture in the wet cake is removed. Step X is performed, for example, by a fluidized drying device. Examples of the fluidized drying device include a rotary kiln and a paddle dryer.
[0065] Specifically, the wet cake is fed into the heating device through an inlet, and the moisture is removed while the wet cake is fluidized. The powder Y that has passed through the fluidized drying device is discharged from the heating device through an outlet.
[0066] The maximum holding temperature in step X is preferably 100° C. or higher, and more preferably 120° C. or higher. The maximum holding temperature is preferably 300° C. or lower, and more preferably 250° C. or lower. The maximum holding temperature is preferably 100-300° C., and more preferably 120-250° C. When the maximum holding temperature is 100° C. or higher, moisture can be appropriately removed, and when the maximum holding temperature is 300° C. or lower, the crystal state of the metal composite hydroxide is unlikely to change.
[0067] The residence time of the wet cake in the heating device in step X is preferably 0.2 hours or more, and more preferably 0.5 hours or more. The residence time is preferably 8 hours or less, and more preferably 6 hours or less. The residence time is preferably 0.2 to 8 hours, and more preferably 0.5 to 6 hours. When the residence time is within the above range, the surface of the metal composite hydroxide is easily scraped to an appropriate degree.
[0068] In step X, the proportion of moisture contained in the wet cake immediately before step X relative to the residence time of the wet cake in the heating device is preferably 10.5 mass% / hour or less, more preferably 10.0 mass% / hour or less, preferably 0.50 mass% / hour or more, and more preferably 0.80 mass% / hour or more. The proportion of moisture contained in the wet cake immediately before step X relative to the residence time of the wet cake in the heating device is preferably 0.50-10.5 mass% / hour, more preferably 0.80-10.0 mass% / hour.
[0069] The wall friction distance of the wet cake in the heating device is preferably 300 to 5000 m. When the wall friction distance is 300 to 5000 m, the surface of the metal composite hydroxide is appropriately scraped. The wall friction distance is calculated by the following method.
[0070] When the wet cake moves due to the movement of the container itself in which the wet cake of the heating device resides, the movement is calculated using the following formula (1). Wall friction distance (m) = circumferential length of the axial cross section of the vessel (m) × vessel peripheral speed (rpm) × residence time (min)…(1)
[0071] When the container of the heating device does not move and the wet cake moves due to the rotation of a rotor inside the container, the calculation is made using the following formula (2). Wall friction distance (m) = perimeter of rotor orbit (m) × circumferential speed of rotor (rpm) × residence time (min) … (2)
[0072] The atmosphere in step X may be air, oxygen, nitrogen, argon, or a mixture of these gases.
[0073] By heating the wet cake while fluidizing it under the above conditions, friction occurs between the particles of the metal composite hydroxide contained in the wet cake and between the particles and the movable surfaces of the wall surface, rotating blades, etc. of the fluidized drying device and the furnace wall. As a result, the surface of the metal composite hydroxide is scraped and becomes smooth. This makes it possible to produce powder Y having a C content and an increase rate of the C content within the above ranges. Furthermore, the amount of residual lithium carbonate in the CAM using powder Y can be reduced, and the initial efficiency of the lithium secondary battery can be improved.
[0074] It is preferable to carry out the step X under conditions such that the proportion of moisture contained in the powder Y immediately after the step X is 1% by mass or less relative to the total mass of the powder Y. The proportion of moisture contained in the powder Y immediately after the step X is preferably 0.9% by mass or less, more preferably 0.8% by mass or less. The lower limit of the moisture proportion is not particularly limited, but is, for example, 0.01% by mass. By carrying out the step X under conditions such that the proportion of moisture contained in the powder Y immediately after the step X is 1% by mass or less, it is possible to produce a powder Y having a C content, a rate of increase in the C content, and a BET specific surface area within the range of this embodiment. The proportion of moisture contained in the powder Y immediately after the step X can be adjusted by the maximum holding temperature, residence time, and wall friction distance in the heating device.
[0075] The powder Y may be sieved after step X.
[0076] The CAM produced using the powder Y produced by the above method can achieve a lithium secondary battery with high initial efficiency.
[0077] The powder Y may be heated before being mixed with the lithium compound described below, and if necessary, multiple heating steps may be performed. In this specification, the heating temperature means the set temperature of the device. In the case of multiple heating steps, the heating temperature means the temperature of the step in which heating is performed at the highest temperature among the steps.
[0078] The heating temperature is preferably 400 - 700 °C, more preferably 450 - 680 °C. When the heating temperature is within the above range, the powder Y is sufficiently oxidized.
[0079] The time for holding at the heating temperature is, for example, 0.1 - 20 hours, preferably 0.5 - 10 hours. The heating rate to the heating temperature is, for example, 50 - 400 °C / hour. As the heating atmosphere, air, oxygen, nitrogen, argon, or a mixed gas thereof can be used.
[0080] The inside of the apparatus may be an appropriate oxygen-containing atmosphere. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and oxygen, or a state in which an oxidizing agent is present under an inert gas atmosphere. When the inside of the apparatus is an appropriate oxygen-containing atmosphere, the transition metal contained in the metal composite hydroxide is appropriately oxidized, and it becomes easier to control the form of the metal composite oxide.
[0081] For the oxygen or oxidizing agent in the oxygen-containing atmosphere, it is sufficient that there are sufficient oxygen atoms to oxidize the transition metal.
[0082] When the oxygen-containing atmosphere is a mixed gas atmosphere of an inert gas and oxygen, the atmosphere inside the apparatus can be controlled by methods such as ventilating oxygen into the heating apparatus or bubbling oxygen into the mixed solution.
[0083] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorate, hypochlorite, nitric acid, halogen, or ozone can be used.
[0084] <Manufacturing method of CAM> The manufacturing method of CAM will be described. The manufacturing method of CAM includes at least firing a mixture of the powder Y obtained in the aforementioned <Manufacturing of powder Y> and a lithium compound.
[0085] (1) Mixing of powder Y and lithium compound This step is a step of mixing a lithium compound and powder Y to obtain a mixture.
[0086] The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride. Among these, lithium hydroxide and lithium carbonate or a mixture thereof are preferred. In addition, when the lithium hydroxide contains lithium carbonate, the content of lithium carbonate in the lithium hydroxide is preferably 5 mass% or less.
[0087] The lithium compound and powder Y are mixed in consideration of the composition ratio of the final target product to obtain a mixture. The amount (molar ratio) of Li relative to the total amount of metal atoms contained in powder Y is preferably 1.00 or more, more preferably 1.02 or more, and even more preferably 1.05 or more. The mixture of the lithium compound and powder Y is fired as described later to obtain a fired product.
[0088] (2) Firing the mixture CAM is obtained by firing a mixture of powder Y and a lithium compound. The firing may have multiple firing stages with different firing temperatures. For example, a first firing stage and a second firing stage in which firing is performed at a higher temperature than the first firing stage may be performed independently. Furthermore, firing stages with different firing temperatures and firing times may be performed. Before the main firing, a preliminary firing may be performed at a temperature lower than the main firing. In addition, after the main firing, a post-firing may be performed at a temperature lower than the main firing.
[0089] In this specification, the firing temperature means the temperature of the atmosphere in the firing furnace, and is the maximum temperature held during the firing process (hereinafter, sometimes referred to as the maximum holding temperature). In the case of a firing process having a plurality of firing stages, the firing temperature means the temperature of the stage in which firing is performed at the highest temperature among the firing stages. The above upper and lower limit values of the firing temperature can be combined arbitrarily.
[0090] The sintering temperature is 400° C. or higher, and preferably 500-1100° C. When the sintering temperature is 400° C. or higher, LiMO having a strong crystal structure can be obtained. Also, when the sintering temperature is 1100° C. or lower, the volatilization of lithium on the particle surface can be reduced.
[0091] The retention time in the firing is preferably 1 to 50 hours. When the retention time in the firing is 1 hour or more, the reaction between the powder Y and the lithium compound can be sufficiently enhanced. When the retention time in the firing is 50 hours or less, the volatilization of lithium ions is unlikely to occur, and the battery performance is improved.
[0092] For the firing, dry air, an oxygen atmosphere, an inert atmosphere, etc. are used depending on the desired composition. In this embodiment, firing in an oxygen atmosphere is preferred.
[0093] The mixture of powder Y and the lithium compound may be sintered in the presence of an inactive flux. The inactive flux may remain in the sintered product, or may be removed by washing with a washing solution after sintering as described below. As the inactive flux, for example, those described in WO2019 / 177032A1 may be used.
[0094] Examples of the firing furnace include a tunnel furnace, a roller hearth kiln, and a rotary kiln.
[0095] As described above, the mixture of powder Y and the lithium compound is fired to obtain CAM. When CAM is produced using the powder Y as a raw material, the amount of residual lithium carbonate can be made less than 0.8% by mass relative to the total mass of CAM. The amount of residual lithium carbonate contained in CAM is more preferably 0.7% by mass or less relative to the total mass of CAM.
[0096] <cam> The CAM of this embodiment is obtained by the <manufacturing method of CAM> using the aforementioned powder Y as a raw material. The amount of residual lithium carbonate in the CAM is reduced, and when the CAM is used, a lithium secondary battery with improved initial efficiency can be easily obtained.
[0097] <Lithium secondary battery> The configuration of a suitable lithium secondary battery when using the CAM will be described. Also, a positive electrode for a lithium secondary battery (hereinafter sometimes referred to as a positive electrode) suitable when using the CAM will be described.
[0098] An example of a lithium secondary battery when using the CAM has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolytic solution disposed between the positive electrode and the negative electrode.
[0099] An example of a lithium secondary battery has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolytic solution disposed between the positive electrode and the negative electrode.
[0100] FIG. 4 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0101] First, as shown in the partial enlarged view of FIG. 4, a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, negative electrode 3 and wound to form an electrode group 4.
[0102] The positive electrode 2 has, as an example, a positive electrode active material layer 2a containing CAM and a positive electrode current collector 2b on which the positive electrode active material layer 2a is formed on one side. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one side of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0103] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.
[0104] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.
[0105] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0106] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.
[0107] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0108] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0109] <All-solid-state lithium secondary battery> Next, a positive electrode using the CAM according to one embodiment of the present invention and an all-solid-state lithium secondary battery including this positive electrode will be described while explaining the configuration of the all-solid-state lithium secondary battery.
[0110] FIG. 5 is a schematic diagram showing an example of the all-solid-state lithium secondary battery of this embodiment. The all-solid-state lithium secondary battery 1000 shown in FIG. 5 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a positive electrode active material and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400. The materials constituting each member will be described later.
[0111] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0112] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0113] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0114] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .
[0115] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.
[0116] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).
[0117] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.
[0118] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in
[0151] to
[0181] of WO2022 / 113904A1 can be used.
[0119] The positive electrode having the above-mentioned configuration has the above-mentioned CAM, and therefore can provide a lithium secondary battery with high initial efficiency.
[0120] Furthermore, the lithium secondary battery having the above-mentioned configuration has a high initial efficiency since it has the above-mentioned positive electrode.
[0121] In another aspect, the present invention includes the following embodiments. [8] Powder Y containing at least Ni, the BET specific surface area of the powder Y being 17-48 m 2 / g, the content of C contained in the powder Y is 0.09 mass% or less with respect to the total mass of the powder Y, and when the powder Y is exposed to the atmosphere for 2 hours, the rate of increase of the content of C is 0.04 mass% / h or less. [9] D of the powder Y 50 Powder Y according to [8], wherein the particle size is 9.5-18 μm.
[10] Powder Y according to [8] or [9], further containing the element M1.
[11] A method for producing CAM, comprising calcining a mixture of powder Y according to any one of [8] to
[10] and a lithium compound.
[12] A method for producing a powder Y, comprising a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni, wherein the BET specific surface area of the powder Y is 17-48 m 2 / g, the content of C contained in the powder Y is 0.09% by mass or less with respect to the total mass of the powder Y, and when the powder Y obtained in the step X is exposed to the atmosphere for 2 hours, the rate of increase in the content of C is 0.04% by mass / h or less.
[13] D of the powder Y 50 The method for producing powder Y according to
[12] , wherein the particle size is 9.5 μm or more and 18 μm or less.
[14] The method for producing powder Y according to any one of
[12] to
[13] , wherein the powder Y further contains the element M1. EXAMPLES
[0122] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.
[0123] <Composition analysis> The composition of Powder Y produced by the method described below was analyzed by the method described above in "Composition Analysis of Powder Y."
[0124] <C content of powder Y and its rate of increase> The C content and its increase rate of the powder Y were measured by the methods described above in (Increase rate of C content) and (Measurement of C content).
[0125] <Cumulative volumetric particle size> Secondary particle diameter D of powder Y 50 was measured by the "cumulative volumetric particle size" method described above.
[0126] <Moisture content> The moisture content of the wet cake and powder Y was measured by the method described above in "Moisture content of wet cake and powder Y".
[0127] <Residual lithium carbonate amount> The amount of residual lithium carbonate contained in the CAM was measured by the method described above in "Amount of Residual Lithium Carbonate."
[0128] <First-run efficiency> Using the CAM obtained by the manufacturing method described below, a lithium secondary battery was produced by the methods described above in (Production of positive electrode for lithium secondary battery) and (Production of lithium secondary battery), and the initial efficiency was measured by the method described in the measurement method for "initial efficiency" above.
[0129] Example 1 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0130] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Co, and Al was 0.88:0.09:0.03.
[0131] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 11.6 (measurement temperature: 40°C), and reaction precipitate 1 was obtained.
[0132] The reaction precipitate 1 was washed with pure water to obtain a wet cake 1, and then dehydrated by suction filtration so that the ratio of the moisture contained in the wet cake 1 to the total mass of the wet cake 1 was 19.2 mass%. The wet cake 1 was charged into a rotary kiln (product name, manufactured by Shimakawa Seisakusho, circumferential length of the firing furnace container is 1.5 m), and the wet cake 1 was heated at a peripheral speed of 2 rpm, a residence time of 5 hours, and 140°C while being fluidized, to obtain a powder 1 containing a metal composite hydroxide 1. At this time, the ratio of the moisture contained in the wet cake 1 to the residence time of the wet cake 1 in the rotary kiln (moisture ratio / residence time) was 3.84 mass% / h, and the wall friction distance of the wet cake 1 in the rotary kiln was 900 m. The ratio of the moisture contained in the powder 1 was 0.72 mass% with respect to the total mass of the powder 1. When the composition of the metal composite hydroxide 1 was analyzed, x=0.12 in the formula (A') and the element M was Co and Al. In formula (B'), y=0.12, z=0, and the element M1 was Co and Al.
[0133] Powder 1 was heated at 650° C. for 5 hours in an air atmosphere and then cooled to room temperature to obtain metal composite oxide powder 1.
[0134] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount 1 of Ni, Co, and Al contained in the metal composite oxide powder 1 was 1.05. Mixture 1 was obtained by mixing the metal composite oxide powder 1 and lithium hydroxide.
[0135] This mixture 1 was calcined at 740° C. for 5 hours in an oxygen atmosphere to obtain CAM-1.
[0136] Example 2 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0137] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of manganese sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Mn, and Al was 0.93:0.035:0.035.
[0138] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 10.8 (measurement temperature: 40°C), and a reaction precipitate 2 was obtained.
[0139] The reaction precipitate 2 was washed with pure water to obtain a wet cake 2, and then dehydrated by suction filtration so that the ratio of moisture contained in the wet cake 2 to the total mass of the wet cake 2 was 5.0 mass%. This wet cake 2 was used and heated under the same conditions as in Example 1, except that the moisture ratio / residence time was 1.00 mass% / h, to obtain a powder 2 containing a metal composite hydroxide 2. The ratio of moisture contained in the powder 2 was 0.50 mass% to the total mass of the powder 2. When the composition of the metal composite hydroxide 2 was analyzed, it was found that in formula (A'), x = 0.07, and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al.
[0140] Powder 2 was heated at 650° C. for 5 hours in an air atmosphere and then cooled to room temperature to obtain metal composite oxide powder 2.
[0141] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li relative to the total amount 1 of Ni, Mn, and Al contained in the metal composite oxide powder 2 was 1.05. Mixture 2 was obtained by mixing the metal composite oxide powder 2 and lithium hydroxide.
[0142] This mixture 2 was calcined at 740° C. for 5 hours in an oxygen atmosphere to obtain CAM-2.
[0143] Example 3 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0144] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of manganese sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Mn, and Al was 0.93:0.01:0.06.
[0145] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 10.8 (measurement temperature: 40°C), and reaction precipitate 3 was obtained.
[0146] The reaction precipitate 3 was washed with pure water to obtain a wet cake 3, and then dehydrated by suction filtration so that the ratio of moisture contained in the wet cake 3 to the total mass of the wet cake 3 was 18.7 mass%. This wet cake 3 was used and heated under the same conditions as in Example 1, except that the moisture ratio / residence time was 3.74 mass% / h, to obtain a powder 3 containing a metal composite hydroxide 3. The moisture ratio contained in the powder 3 was 0.66 mass% to the total mass of the powder 3. When the composition of the metal composite hydroxide 3 was analyzed, it was found that in formula (A'), x = 0.07, and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al.
[0147] The same procedure as in Example 2 was carried out using Powder 3 to obtain CAM-3.
[0148] Example 4 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0149] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of aluminum sulfate such that the molar ratio of Ni, Co, and Al was 0.88:0.09:0.03.
[0150] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 12.2 (measurement temperature: 40°C), and reaction precipitate 4 was obtained.
[0151] The reaction precipitate 4 was washed with pure water to obtain a wet cake 4, and then dehydrated by suction filtration so that the ratio of moisture contained in the wet cake 4 to the total mass of the wet cake 4 was 15.5 mass%. This wet cake 4 was heated under the same conditions as in Example 1, except that the moisture ratio / residence time was 3.10 mass% / h, to obtain a powder 4 containing a metal composite hydroxide 4. The moisture ratio contained in the powder 4 was 0.17 mass% to the total mass of the powder 4. When the composition of the metal composite hydroxide 4 was analyzed, it was found that in formula (A'), x = 0.12, and the element M was Co and Al. In formula (B'), y = 0.12, z = 0, and the element M1 was Co and Al.
[0152] Powder 4 was used and the same procedure as in Example 1 was carried out to obtain CAM-4.
[0153] Comparative Example 1 The wet cake 1 was placed in a static calcination furnace (product name, manufactured by Daito Co., Ltd.) and heated at 125°C for 24 hours to obtain a powder C1 containing a metal composite hydroxide C1. The proportion of water contained in the powder C1 was 0.56 mass% relative to the total mass of the powder C1. The powder C1 was used and the subsequent operations were the same as those in Example 1 to obtain CAM-C1.
[0154] Composition analysis of the metal composite hydroxide C1 revealed that in formula (A'), x = 0.12, and the element M was Co and Al. In formula (B'), y = 0.12, z = 0, and the element M1 was Co and Al.
[0155] Comparative Example 2 The wet cake 2 was placed in a static calcination furnace (product name, manufactured by Daito Co., Ltd.) and heated at 125°C for 24 hours to obtain powder C2 containing metal composite hydroxide C2. The moisture content of powder C2 was 0.81 mass% relative to the total mass of powder C2. Powder C2 was used and the same operations as in Example 1 were carried out thereafter to obtain CAM-C2. When the composition of metal composite hydroxide C2 was analyzed, it was found that in formula (A'), x = 0.07, and element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and element M1 was Mn and Al.
[0156] Comparative Example 3 Water was placed in a reaction vessel equipped with a stirrer and an overflow pipe, and then an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 70°C.
[0157] A mixed solution was prepared by mixing an aqueous solution of nickel sulfate, an aqueous solution of cobalt sulfate, and an aqueous solution of manganese sulfate such that the molar ratio of Ni, Co, and Mn was 0.83:0.12:0.05.
[0158] Next, in the reaction vessel, an aqueous solution of ammonium sulfate was continuously added as a complexing agent to the mixed solution while stirring. An aqueous solution of sodium hydroxide was added dropwise at appropriate times so that the pH of the mixed solution in the reaction vessel became 11.2 (measurement temperature: 40°C), and a reaction precipitate C3 was obtained.
[0159] The reaction precipitate C3 was washed to obtain a wet cake C3, and then dehydrated by suction filtration so that the ratio of moisture contained in the wet cake C3 to the total mass of the wet cake C3 was 30.0 mass%. This wet cake C3 was heated under the same conditions as in Example 1, except that the moisture ratio / residence time was 6.00 mass% / h, to obtain a powder C3 containing a metal composite hydroxide C3. The moisture ratio contained in the powder C3 was 5.0 mass% to the total mass of the powder C3. When the composition of the metal composite hydroxide C3 was analyzed, it was found that in formula (A'), x = 0.17, and the element M was Co and Mn. In formula (B'), y = 0.17, z = 0, and the element M1 was Co and Mn.
[0160] Powder C3 was heated at 650° C. for 5 hours in an air atmosphere and then cooled to room temperature to obtain metal composite oxide powder C3.
[0161] Lithium hydroxide was weighed out so that the amount (molar ratio) of Li was 1.05 relative to the total amount of Ni, Co, and Mn contained in the metal composite oxide powder C3, which was 1. The metal composite oxide powder C3 and lithium hydroxide were mixed to obtain a mixture C3.
[0162] This mixture C3 was calcined at 740° C. for 5 hours in an oxygen atmosphere to obtain CAM-C3.
[0163] Comparative Example 4 The wet cake 2 was dehydrated by suction filtration so that the ratio of the moisture contained in the wet cake 2 to the total mass of the wet cake 2 was 16.5 mass%. The wet cake 2 was charged into a rotary kiln (product name, manufactured by Shimakawa Manufacturing Co., Ltd., the circumference length of the container of the firing furnace was 1.5 m), and the wet cake 2 was heated at 140 ° C. with a peripheral speed of 2 rpm, a residence time of 1 hour, a moisture ratio / residence time of 16.50 mass% / h, while flowing, to obtain a powder C4 containing a metal composite hydroxide C4. At this time, the wall friction distance of the wet cake 2 in the rotary kiln was 180 m. The ratio of the moisture contained in the powder C4 was 7.2 mass% with respect to the total mass of the powder C4. When the composition of the metal composite hydroxide C4 was analyzed, x = 0.07 in formula (A'), and the element M was Mn and Al. In formula (B'), y = 0.07, z = 0, and the element M1 was Mn and Al. The same procedure as in Example 2 was then carried out using powder C4 to obtain CAM-C4.
[0164] For powders 1 to 4 of Examples 1 to 4 and powders C1 to C4 of Comparative Examples 1 to 4, y and z in formula (B'), the C content, the rate of increase in the C content, the BET specific surface area (referred to as BET in the table), and D 50 Table 1 shows the amount of residual lithium carbonate in CAM1 to CAM-4 and CAM-C1 to CAM-C4, and the initial efficiency of the lithium secondary battery produced using each CAM.
[0165] [Table 1]
[0166] In the powders 1 to 4 of Examples 1 to 4, the rate of increase in the C content was less than 0.05 mass% / h, the C content was 0.1 mass% or less, and the BET specific surface area was 10 m 2 / g. Furthermore, the amount of residual lithium carbonate in CAM-1 to CAM-4 was less than 0.8 mass %, and the initial efficiency of lithium secondary batteries using these was 85% or more.
[0167] On the other hand, in Comparative Examples 1, 2, and 4, the C content was 0.1 mass% or more, the amount of residual lithium carbonate in CAM-C1 or CAM-C2 was 0.8 mass% or more, and the initial efficiency of the lithium secondary batteries using these was 78.6 to 79.6%. Also, in Comparative Examples 1 and 3, the rate of increase in the C content was 0.05 mass% / h or more, the amount of residual lithium carbonate in CAM-C1 or CAM-C3 was 0.8 mass% or more, and the initial efficiency of the lithium secondary batteries using these was 78.6 to 83.3%. [Industrial Applicability]
[0168] According to the present invention, there are provided a method for producing Powder Y, CAM, and a method for producing Powder Y, which enable a lithium secondary battery with high initial efficiency to be obtained. [Explanation of symbols]
[0169] Reference Signs List 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery< / cam>
Claims
1. A metal composite hydroxide powder containing at least Ni, the metal composite hydroxide powder having a BET specific surface area of 10 m 2 / g or more, The content of carbon atoms (C) contained in the metal composite hydroxide powder is 0.1 mass% or less based on the total mass of the metal composite hydroxide, The metal composite hydroxide powder, when exposed to the atmosphere for 2 hours, has a rate of increase in the C content of less than 0.05 mass% / h.
2. The metal composite hydroxide powder according to claim 1, wherein the average secondary particle size of the metal composite hydroxide powder is 5 μm or more and 20 μm or less.
3. The metal composite hydroxide powder according to claim 1 or 2, further containing an element M, wherein the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P.
4. A method for producing a positive electrode active material for a lithium secondary battery, comprising calcining a mixture of the metal composite hydroxide powder according to claim 1 or 2 and a lithium compound.
5. A method for producing a metal composite hydroxide powder, comprising: a step X of heating a wet cake containing a metal composite hydroxide containing at least Ni, The BET specific surface area of the metal composite hydroxide powder is 10 m 2 / g or more, The content of carbon atoms (C) contained in the metal composite hydroxide powder is 0.1 mass% or less based on the total mass of the metal composite hydroxide, The method for producing a metal composite hydroxide powder, wherein when the metal composite hydroxide powder obtained in the step X is exposed to the atmosphere for 2 hours, the rate of increase in the C content is less than 0.05 mass% / h.
6. The method for producing a metal composite hydroxide powder according to claim 5, wherein the average secondary particle size of the metal composite hydroxide powder is 5 μm or more and 20 μm or less.
7. 7. The method for producing a metal composite hydroxide powder according to claim 5 or 6, wherein the metal composite hydroxide powder further contains an element M, and the element M is one or more elements selected from the group consisting of Co, Mn, Al, Fe, Cu, Ti, Mg, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, S and P.
Citation Information
Patent Citations
Process for manufacturing positive electrode active material for lithium secondary battery, and active material precursor powder to be used therein
WO2014061580A1